Finite element analysis of the buckling of rectangular composite plates in compression - Zhang, Hao (Nanyang Technological University, 2024)
This project is designed to investigate the buckling behavior of a rectangular plate under compressive load. The rectangular plate was modeled and analyzed using the finite element analysis software ANSYS Workbench (academic 2023 R1). It simulates an Anti-Symmetric Angle-Ply composite plate with various aspect ratios, stacking angles, and boundary conditions. The report analyzed the simulation results and determined the plate's coupling effects. The boundary conditions involved in the projects are simple support boundary conditions only. They are renamed as S1, S2, S3, and S4. Their purpose is to constrain the motion of the plate in the x and y directions. S1 constrained the movement in both directions, S2 limited the displacement in the y direction, S3 blocked the motion in the x direction, and S4 had no constraints. The stacking sequence of the composite plate varies from 2 to 8 plies, the stacking angle started from 0˚ and ended at 90˚ with an increment of 15˚. The ANSYS simulation showed that the rectangular composite plate in the S1 boundary condition has the relatively highest non-dimensional buckling force, and the bucking response for the plate in the remaining 3 boundary conditions depends on the aspect ratio and stacking angles. Therefore, the plate in the S1 boundary condition has the relatively lowest coupling effects among the 4 boundary conditions. In addition, the results revealed that the coupling effect is inverse-proportional to the number of plates, it decreases with the increase in plate number. Future improvements for this project include redesigning the ANSYS model or validating the results by applying it to other FEA software, such as ABAQUS and NX Nastran.